Applied Mechanics Against the Arts of Geotechnical and Coastal Engineering - Sawicki, A. (Engineering Transactions, 2004)
This essay deals with interactions between applied mechanics and geotechnical and coastal engineering. Its aim is to answer some basic questions concerning the influence of applied mechanics on the above specializations and vice versa, as well as to identify practical problems which could be inspiring for applied mechanics. The above problems are discussed within the framework of soils' plasticity and mechanics of mixtures.